Companies Law No. 159/1981 As amended by Laws Nos. 230/1989, 212/1994, 3/1998, 159/1998, and 94/2005 / Translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Law No. 159 of the year 1981 promulgating the law of the joint-stock companies, partnerships limited by shares and the limited liability companies. Part 1: General provisions. - Chapter - 1: The companies governed by the provisions of this law. Chapter – 2: Incorporation. - First: Founders. - Second: Incorporation procedures. - Third: Provisions governing the incorporation of the different types of companies. -- Part - 2: The provisions concerning the types of companies. - Chapter - 1: Joint-stock companies. - First: Financial structure. - Second: Company's management. - Third: Auditors. - Chapter 2: Partnerships limited by shares. - Chapter - 3: The limited liability companies. -- Part-3: Merger and the changing of the company's form. -- Part - 4: Liquidation of the company -- Part - 5: Control, inspection, and penalties. -- Part - 6: The representation branches and offices of foreign companies in Egypt. -- Part-7: Final provisions